2020
DOI: 10.1080/15230430.2020.1822728
|View full text |Cite
|
Sign up to set email alerts
|

The end of the eternal snows: Integrative mapping of 100 years of glacier retreat in the Venezuelan Andes

Abstract: Venezuela will soon become the first Andean country to lose all of its glaciers, as the "eternal snows" of the Sierra Nevada de Mérida (SNM) disappear. Although documentation of glacier retreat in Venezuela commenced over a century ago, an updated reconstruction at sufficient spatial resolution is warranted. Our objectives were to (a) produce detailed multitemporal maps of glacier cover in the SNM since 1952 and revise historical estimates for 1910 and (b) document changes in cover and rates of glacier retreat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 63 publications
1
17
0
1
Order By: Relevance
“…Venezuela will soon be the first Andean country to lose all of its glaciers. Ramírez et al (2020) showed that glaciers in the Sierra Nevada de Mérida, where the highest peaks in the country are located, have lost 99% of their area since 1910. There is only one remaining ice mass at Humboldt Peak (4,942 m asl), which has lost 98.7 % of its surface since 1910, with an area for 2019 of only 0.0454 Km 2 (Ramírez et al, 2020).…”
Section: Study Areamentioning
confidence: 99%
“…Venezuela will soon be the first Andean country to lose all of its glaciers. Ramírez et al (2020) showed that glaciers in the Sierra Nevada de Mérida, where the highest peaks in the country are located, have lost 99% of their area since 1910. There is only one remaining ice mass at Humboldt Peak (4,942 m asl), which has lost 98.7 % of its surface since 1910, with an area for 2019 of only 0.0454 Km 2 (Ramírez et al, 2020).…”
Section: Study Areamentioning
confidence: 99%
“…In this region of South America, glaciers lost 1.0 ± 05 Gt/year between 2000 and 2018 (Dussaillant et al 2019 ). One of the most dramatic examples of the consequences of global warming on the cryosphere can be found in Venezuela, the first country in the world to have lost all of its glaciers (Braun and Bezada 2013 ; Ramírez et al 2020 ) (Fig. 1 ).…”
Section: Glacier Thawingmentioning
confidence: 99%
“…a La Corona glacier, then covering Humboldt and Bonpland peaks, seen from Pico Espejo in 1910 (Jahn 1925); b Same view in 2019 ( Copyright Luis Daniel Llambí, with permission). c Surface area for La Corona glacier (covering Humboltd and Bonpland peaks) between 1910 and 2019 (Copyright Alejandra Melfo, adapted from Ramírez et al 2020 ) …”
Section: Glacier Thawingmentioning
confidence: 99%
See 2 more Smart Citations